THE IMPACT OF GREEN ACCOUNTING IMPLEMENTATION AND PROFITABILITY ON FIRM VALUE IN ENERGY SECTOR COMPANIES - Hutagaol, Rafael; Pratama, Mar'elfan Hadi; Ether, Christian; Maithy, Sifera Patricia (LPPM Universitas Bina Bangsa, 2025)
This study aims to test and analyze the effect of Green Accounting implementation and Profitability on Firm Value. This study uses secondary data, namely, financial reports and annual reports of companies. This study surveyed 16 Energy Sector Companies listed on the IDX between 2021 and 2023. The sampling technique used was purposive sampling. The research data were analyzed using multiple linear regression analysis using a statistical application, IBM SPSS 25. The study results show that Green Accounting has a significant effect on Firm Value and Profitability and also has a significant effect on Firm Value. Both variables simultaneously have a significant effect on Firm Value.